2022
DOI: 10.1101/2022.03.25.485421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two modes of mid-frontal theta suggest a role in conflict and error processing

Abstract: Mid-frontal theta is well-known to be involved in conflict and error-processing. In paradigms known to evoke response conflict, the temporal sequence of events leading up to conflict or error resolution and theta's involvement in such scenarios is not well understood. Using single-trial analyses of electrophysiological data from participants performing the Flanker (N = 28) and Simon paradigm (N = 18), we probed the relationship between transient theta activity and the underlying metrics of response conflict. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…On a theoretical level, rise-to-threshold models suggest that the increase in theta activity adjusts response thresholds or "hold your horses" recruitment of cognitive control (Cavanagh and Frank, 2014, Frank et al, 2005. Using a Flanker and Simon task, Muralidharan et al (2023) found that theta events (i.e., transient theta events in single trials) could be dissociated into two modes when a partial error occurred. Here, one mode of theta was linked to the stimulus-response conflict possibly reflecting a caution signal that "holds" responses.…”
Section: Time-frequency Decomposition Of Midfrontal Eeg Signals Has R...mentioning
confidence: 99%
“…On a theoretical level, rise-to-threshold models suggest that the increase in theta activity adjusts response thresholds or "hold your horses" recruitment of cognitive control (Cavanagh and Frank, 2014, Frank et al, 2005. Using a Flanker and Simon task, Muralidharan et al (2023) found that theta events (i.e., transient theta events in single trials) could be dissociated into two modes when a partial error occurred. Here, one mode of theta was linked to the stimulus-response conflict possibly reflecting a caution signal that "holds" responses.…”
Section: Time-frequency Decomposition Of Midfrontal Eeg Signals Has R...mentioning
confidence: 99%